Legal Politics, Tourism Village, Cultural Tourism - I Wayan Wesna Astara (Sociological Jurisprudence Journal, 2024)
Legal Politics and social changes in Bali Tourism Tourism Villages have provided Balinese people, especially Indigenous Balinese, to develop cultural tourism. The majesty of Balinese Hindu cultural values is not only recognized by the Republic of Indonesia, even the world recognizes it by providing protection for Balinese Hindu cultural and cultural values such as Balinese irrigation (subak). Therefore, legal protection for the people of Bali, especially tourism villages in Bali which are based on Hinduism, local traditions, customs and Balinese culture, is important and very relevant for research. The purpose of this research is to find out a new value for the concept of cultural tourism in managing tourism villages in Bali. The value of local wisdom in tourism management if the state and indigenous peoples in Bali are unable to provide protection, then the sustainability of cultural tourism will be threatened. Traditional villages in Bali have the potential to develop culture-based tourism. For this reason, this paper examines the potential for rural tourism (ecotourism) in various regencies in Bali, especially Badung, Tabanan, Bangli regencies, then legal politics related to cultural tourism will be the focus of this writing. The research method used is empirical legal research, with legal anthropology and legal sociology approaches. The research results show that legal politics towards tourism villages can be realized in the form of legislation, Bali Province Regional Regulations, Regency/City Regional Regulations and/or Regent Regulations and others. Cultural tourism arrangements are contained in the Regional Regulation of the Province of Bali Number 5 of 2020 concerning cultural tourism standards. The impact of the implementation of the regional regulations mentioned above, there has been a social change in the management of culture-based tourism villages in each traditional village in Bali. In this case, it is managed by the Institution, namely Traditional village-owned enterprise (referred to as BUPDA) as an instrument for the welfare of the Balinese indigenous people in managing Cultural Tourism. If necessary, traditional villages can work together with (private) investors using BOT agreements to strengthen cultural tourism